Assessing the appropriateness of the management of otitis media in Australia: A population‐based sample survey. (17th July 2019) - Clay‐Williams, Robyn; Stephens, Jacqueline H; Williams, Helena; Hallahan, Andrew; Dalton, Chris; Hibbert, Peter; Ting, Hsuen P; Arnolda, Gaston; Wiles, Louise; Braithwaite, Jeffrey; ,
Abstract : Aim: Acute otitis media (AOM) is the most common infectious disease for which antibiotics are prescribed; its management is costly and has the potential to increase the antimicrobial resistance of this infection. This study measured the levels of adherence to the clinical practice guidelines (CPGs) of AOM and otitis media with effusion (OME) management in Australian children. Methods: We searched for national and international CPGs relating to AOM and OME in children and created 37 indicators for assessment. We reviewed medical records for adherence to these indicators in 120 locations, across one inpatient and three ambulatory health‐care settings. Our review sample was obtained from three Australian states that contain 60% of the nation's children. Results: We reviewed the records of 1063 children with one or more assessments of CPG adherence for otitis media. Of 22 indicators with sufficient data, estimated adherence ranged from 7.4 to 99.1%. Overuse of treatment, particularly overprescribing of antibiotics, was more common than underuse. A frequent lack of adherence with recommended care was observed for children aged between 1 and 2 years with AOM. Adherence varied by health‐care setting, with emergency departments and inpatient settings more adherent to CPGs than general practices. Conclusions: Our assessment of a number of indicators in the common settings in which otitis media is treated found that guideline adherence varied widely between individual indicators. Internationally agreed standards for diagnosis and treatment, coupled with clinician education on the existence and content of CPGs and clinical decision support, are needed to improve the management of children presenting with AOM and OME.